A Prospective Study of Early Loaded Single Implant-Retained Mandibular Overdentures: Preliminary One-Year Results - Ali M. El-Sheikh; Omar F. Shihabuddin; Sahar M. F. Ghoraba (International Journal of Dentistry)
Purpose. To investigate the predictability of simplifying mandibular overdenture treatment using one-stage surgery and early prosthetic loading of a single implant. Materials and Methods. Twenty edentulous patients with problematic existing mandibular dentures were treated. A single implant with a chemically modified surface (SLActive, Straumann AG, Basel, Switzerland) was placed into the mandibular midline. The patients were recalled at 3, 6 and 12 months. Clinical assessments and marginal bone loss using standardized radiographs were recorded. All complications, failures and maintenance were noted. Visual analog-scale questionnaires were used to record patient satisfaction in five categories. ANOVA was used to determine differences between means of marginal bone loss and different categories of patient staisfaction (𝑃=0.05). Results. The 20 early loaded implants were all surviving at the 12-month recall. All implants showed less than 1 mm of marginal bone loss by the end of the 1-year with a significant increase during the follow-up period. Few prosthetic problems were reported. Patient satisfaction was high with a significant increase in all comfort and functional parameters. Conclusions. These preliminary 1-year results indicate that early loading of a single chemically modified surface implant used to retain a mucosa-borne mandibular overdenture is a safe, reliable, and cost-effective treatment.